Mechanical, thermal and antimicrobial properties of PLA/jackfruit skin composites containing thymol and nanocellulose - N'a, Zabidi; M.S.A, Fuad; I.S.M.A, Tawakkal; M.S.M, Basri; S.H, Othman (Elsevier BV, 2023)
Polylactic acid (PLA) and jackfruit waste, particularly jackfruit skin powder (JSP), are promising alternatives to produce active bionanocomposite films. The films were characterized by mechanical, thermal, and antimicrobial properties. The presence of nanocellulose (NC) had more remarkable impacts on the tensile strength of neat PLA, and PLA/JSP, meanwhile addition of thymol EO led to an improvement in flexibility. The thermal degradation profile revealed the maximum degradation temperature of PLA and PLA/JSP with 3% NC shifted to a higher temperature indicating better thermal stability. The PLA/JSP composite with 5% loading of NC showed synergistic antibacterial efficiency since it promoted inhibition against S. Aureus. Therefore, this work may offer good potential for food packaging application, being an alternative to the environmental issue of conventional petroleum-based plastics.